2017
DOI: 10.1194/jlr.m078980
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin regulates the cross-talk between phosphatidylcholine and cholesterol metabolism in mouse liver

Abstract: Osteopontin (OPN) is involved in different liver pathologies in which metabolic dysregulation is a hallmark. Here, we investigated whether OPN could alter liver, and more specifically hepatocyte, lipid metabolism and the mechanism involved. In mice, lack of OPN enhanced cholesterol 7α-hydroxylase (CYP7A1) levels and promoted loss of phosphatidylcholine (PC) content in liver; in vivo treatment with recombinant (r)OPN caused opposite effects. rOPN directly decreased CYP7A1 levels through activation of focal adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
(62 reference statements)
2
23
0
Order By: Relevance
“…The results showed a positive correlation between serum OPN concentration and age (Figure 1a). Given that OPN is increased in liver (Lima‐Cabello et al, 2010) and serum of NAFLD patients (Nunez‐Garcia et al., 2017), OPN levels were also measured in a cohort of NAFLD patients ( n = 89) (Figure 1b) (Table 1). The correlation between serum OPN concentration and age was lost in NAFLD patients, in which OPN levels were already high in younger patients (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed a positive correlation between serum OPN concentration and age (Figure 1a). Given that OPN is increased in liver (Lima‐Cabello et al, 2010) and serum of NAFLD patients (Nunez‐Garcia et al., 2017), OPN levels were also measured in a cohort of NAFLD patients ( n = 89) (Figure 1b) (Table 1). The correlation between serum OPN concentration and age was lost in NAFLD patients, in which OPN levels were already high in younger patients (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Osteopontin (OPN) is a multifunctional protein that is expressed in a variety of tissues and has many functions, both physiological and pathological (Ashkar et al, 2000; Ramaiah & Rittling, 2007). It is involved in liver pathologies and acts as a modulator of liver lipid metabolism (Nunez‐Garcia et al., 2017; Nuñez‐Garcia et al, 2018). OPN is involved in NAFLD pathogenesis (Kiefer et al., 2011), and its liver expression is increased in obesity and correlates with steatosis and insulin resistance (Gómez‐Ambrosi et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also modulates the activation and proliferation of several cell types during regeneration 16 . Recently, we reported that OPN controls de novo FA synthesis in hepatocytes and that liver PC concentration is regulated by circulating OPN 17 . In fact, high levels of OPN increase liver PC concentration, while PC concentration is low in OPN deficient mice 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that OPN controls de novo FA synthesis in hepatocytes and that liver PC concentration is regulated by circulating OPN 17 . In fact, high levels of OPN increase liver PC concentration, while PC concentration is low in OPN deficient mice 17 . We also found that inhibiting de novo cholesterogenesis, which is increased in OPN-KO mice liver, results in the restoration of PC concentration in OPN-KO mice, exemplifying the cross-talk between these metabolic pathways 17 .…”
Section: Introductionmentioning
confidence: 99%